2006
DOI: 10.1111/j.1745-6584.2006.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Long‐Term Remedial Costs by Transport Modeling Optimization

Abstract: The Department of Defense (DoD) Environmental Security Technology Certification Program and the Environmental Protection Agency sponsored a project to evaluate the benefits and utility of contaminant transport simulation-optimization algorithms against traditional (trial and error) modeling approaches. Three pump-and-treat facilities operated by the DoD were selected for inclusion in the project. Three optimization formulations were developed for each facility and solved independently by three modeling teams (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Becker et al, 2006;Wang et al, 2009;Yang and Cai, 2010;Yin et al, 2012), they are often limited by the ability to model these systems properly. In addition, the decision variables, objective functions and constraints are generally assumed to be known (e.g.…”
Section: Current Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Becker et al, 2006;Wang et al, 2009;Yang and Cai, 2010;Yin et al, 2012), they are often limited by the ability to model these systems properly. In addition, the decision variables, objective functions and constraints are generally assumed to be known (e.g.…”
Section: Current Statusmentioning
confidence: 99%
“…Even when optimisation is undertaken, the process could be considered to be fluid and iterative. For example, Becker et al (2006), in an application of EAs to three real-world groundwater remediation sites, found that decision makers often asked for modifications to the formulations (e.g. new constraints) after viewing initial results that gave new insights into the remediation systems.…”
Section: Development Of Understanding Of Limitations and Strategies Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated an ANN methodology as a groundwater simulator in the optimization model. An ANN embedded within an optimization model can accurately predict ground water state in response to management alternatives (Rogers and Dowla 1994;Rao et al 2005;Becker et al 2006;Coppola et al 2007;Chu and Chang 2009a). Rogers and Dowla (1994) used an ANN-Genetic Algorithm (GA) methodology to replace a traditional simulation-optimization model.…”
mentioning
confidence: 99%
“…The ANN-GA methodology optimizes the set of pumping patterns for meeting remediation objectives (Rogers et al 1995). Becker et al (2006) coupled optimization and transport simulation models to three pump-andtreat systems for real problems. They used ANN-derived state transition equations to replace time-consuming simulation models in the optimization algorithm.…”
mentioning
confidence: 99%